(untitled) (Journal of Geography and Environmental Management, 2019)
This article considers climatic conditions of atmospheric droughts in the territory of North Kazakhstan in the period from 1971 to 2000. Index of atmospheric aridity of P.A. Pedya was applied to characterize intersity of droudhts in North Kazakhstan are more frequent than average droughts, and severe droughts are extremely rare.